The disruption of birds' double mutualistic interactions in novel ecosystems - Nereu, Mauro Guilherme Pereira (2024)
Non-native trees disrupt ecological processes vital to native plant communities. We studied how forests dominated by Acacia dealbata and Eucalyptus globulus affect the role of birds as dual pollinators and seed dispersers in a region heavily impacted by these two non-native species. We compared bird-plant interactions in the native and in the two non-native forest types. We constructed a multilayer regional network for each forest type and evaluated differences in network dissimilarity between networks. We also calculated the bird's importance in connecting processes and variables associated with module diversity. To determine how the networks react to changes in species richness, we did a simulation of species richness gradient and link percentage for each forest type. The number of birds acting both as pollinators and seed dispersers was higher in native than in non-native forests. However, birds in non-native forests still play a crucial role in maintaining the ecological services provided to native plant communities. However, the eucalyptus network exhibited a concerning simplification, forcing bird species to fully exploit the few remaining resources, leaving little room for structural adjustments and limiting the ecosystem's ability to withstand further species loss. These findings highlight how non-native trees may trigger cascading effects across trophic levels.